Ayahuasca may help to improve self‐compassion and self‐criticism capacities. (19th August 2021) - Domínguez‐Clavé, Elisabet; Soler, Joaquim; Elices, Matilde; Franquesa, Alba; Álvarez, Enric; Pascual, Juan C.
Abstract: Objective: Ayahuasca is a psychedelic brew that originated in the Amazon basin. The psychological effects of this drug are becoming better understood due to the growing research interest in identifying new potential therapeutic agents for the treatment of emotion dysregulation and other disorders. Previous studies suggest that ayahuasca enhances mindfulness‐related capacities (decentering, non‐judging, non‐reacting and acceptance) and emotion regulation. The aim of the present exploratory study was to determine the effects of ayahuasca on self‐compassion in a community sample. Methods: We administered validated questionnaires (the Self‐Compassion Scale‐Short Form and Forms of Self‐Criticism and Self‐Reassurance) to evaluate pre‐post changes in self‐compassion and self‐criticism/self‐reassurance in 45 volunteers (27 women; 60%) before and after (≤24 h) an ayahuasca ceremony. Most participants ( n = 29; 67.4%) had previously used ayahuasca. Results: Ayahuasca resulted in significant improvements, with medium to large effect sizes ( η 2 = 0.184–0.276), in measures of self‐compassion ( p < 0.05), self‐criticism ( p < 0.01) and self‐reassurance ( p < 0.01). Conclusions: The findings of this study suggest that ayahuasca promotes well‐being and self‐compassion, which could have a therapeutic effect on individuals with negative affect and other psychopathological conditions. Large, controlled studies are needed to confirm these findings.